Genetic parameters of milk mid-infrared spectra and their genetic relationships with milk production and feed efficiency traits in French Lacaune dairy sheep - C. Machefert; C. Robert-Granié; J.M. Astruc; H. Larroque (Journal of Dairy Science)
ABSTRACT: In French dairy sheep, Fourier transform infrared (FTIR) milk spectral data routinely predict the major milk components used in national genetic evaluations. The direct influence of genetic and environmental factors on milk FTIR spectra has been widely studied in dairy cattle, with relatively little focus on dairy ewes. In this study, 36,873 milk test-day records were available for 4,712 French Lacaune ewes farmed on 8 commercial farms. Our main goals were to provide the first description of spectral data and estimate the genetic parameters of French Lacaune dairy sheep during lactation. Principal component analysis results demonstrated the impact of lactation period on specific wavenumbers, allowing the identification of FTIR spectra collected at early (mo 2–4) and late (mo 5–7) lactation stages. The average estimated heritability (± mean SE) of the FTIR milk spectra from 2,971 to 926 cm−1 (446 wavenumbers) was 0.29 ± 0.02, ranging from 0.13 ± 0.01 to 0.42 ± 0.02. Furthermore, the heritabilities of spectra collected at the beginning or end of lactation changed at each point of the spectrum. However, at each wavenumber, the genomic correlation of transmittance values between these 2 lactation periods was high (>0.77), indicating the absence of a genotype–environment interaction. The genomic correlations between spectral regions and milk production traits (i.e., daily milk yield, fat and protein content, SCS) varied from moderate to high. The results suggested that the most heritable areas of the spectrum were also genetically associated with dairy traits. Finally, the genomic correlations observed between the ewes' feed efficiency traits and the FTIR spectrum were moderate to high, whereas the genomic correlations between the change in body condition score and spectral data were rather low to moderate. This study confirmed that spectral data from Lacaune ewe milk were heritable, evolved phenotypically and genetically during lactation, and were genetically correlated with traits included in breeding goals or traits of interest to the dairy industry.